COLABORATIVE BADAN PENAGGULANGAN BENCANA DAERAH KOTA DUMAI DALAM MENAGGULANGI KEBAKARAN LAHAN DI KOTA DUMAI - S, Rizky Setiawan (UIR PRESS, 2019)
Forest and land fire control is generally carried out through efforts to prevent, extinguish, and handle post-fire carried out at the national level to the level of forest management unit. Fire prevention efforts are carried out through public awareness campaigns; improvement of prevention technology, such as warning and prevention of forest fires, such as reservoirs, green belts, control towers, and others; and software stabilization. The handling of land fire disasters is of particular concern by the central government and regional governments. According to the Ministry of Environment and Forestry (KLHK), based on Landsat satellite imagery up to September 2019, forest and land fires reached 857,755 hectares. For mineral land 630,451 hectares, and 227,304 hectares of peatland. Dumai in 2019 experienced a land deed with a land area of ​​about 192.25 hectares with coverage of the nine river districts, West Dumai, south Dumai, Medangkampai, East Dumai and Bukir Kapur. report from the Dumai City Environment Agency Air Quality Index, Wednesday (18/9) at 07.00 at the level of 500 PSI (695 Pm10 / 698 Pm2.5), dangerous status. Dumai currently has 10 hotspots detected at the 70 percent confidence level, while at the 75 percent confidence level. In accordance with the mayor's regulation number 71 of 2016 concerning the position, organizational structure, duties and functions as well as the work procedures of the Dumai City Regional Disaster Management Agency article 7 point 2, the task of carrying out integrated disaster management includes: 1. Pre-disaster, 2. Emergency response, 3. Post-disaster has not been optimally carried out by disaster management agencies. In order to optimize the handling of land fires in the Dumai City area, the Government of the City of Dumai in particular the Regional Disaster Management Agency seeks in the form of socialization of prevention and suppression of land fires. To realize the handling of land fires, there needs to be collaborative among related institutions, namely the regional government, military, police and other agencies. In the opinion of Ansell and Gash collaborative governance is a process of collaborative activities by regulating a decision in the policy process carried out by several public institutions with other parties involved and directly or indirectly involved with the aim of resolving public problems.